Study Of Entrepreneurship Use of Zakat as an Effort to Increase Empowerment Community Economy : Study on Indonesian Zakat Initiatives, DKI Jakarta - Wiwin; Windianingsih, Agustin; Santoso, Rukun (CV ODIS, 2021)
In view of the foundation and issue restrictions over, the author for this situation plans the issue to be examined so as to restrict the conversation that is excessively wide. The plan of the issue is: (1) Provide contribution to the Amil Zakat Institution with respect to the improvement of a gainful zakat usage model; (2) Provide contribution on the advancement of business venture preparing techniques to improve mustahik business the executives aptitudes; (3) Provide input with respect to the advancement of business venture preparing strategies to increment mustahik pay; and (4) Finding choices to improve the nature of mustahik in dealing with the business by helping out the Ministry of Cooperatives and UKMs. IZI has a significant function in overseeing UKM entertainers with the goal that the objective of zakat as an answer for tackle the monetary issues of individuals is accomplished and an ever-increasing number of individuals will depend the dispersion of their zakat assets to proficient, imaginative and focused on Zakat Institutions